The Effect of Touch of The Ball in Small Side Games on The Improvement Vo2max Amateur Football Players (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The aims of this study was: (1) the effect of training the small side games 4v4 two-touch game against VO2max, (2) the effect of training small side games 4v4 free touch against VO2max, and (3) the different effect between small side games 4v4 two touches and small side games 4v4 free touch against VO2max. This research is an experimental research with a modified pre-test – post-test group design. The subjects of this research were 32 amateur football players. MFT was used to measure VO2max in data collecting technique. The data were analyzed by using t-statistical calculation assisted with SPSS 16.0 at 0.05 significance level. The result shows the exercise of small side games 4v4 two touches affected to VO2max (sig value = 0.000), training of small side games 4v4 free touch affected to VO2max (sig value = 0,016) and there are some differences between two touches and free touch training. Coaches are suggested to use small side method in order to improve the VO2max of their players.